Isolation and characterization of Listeria Monocytogenes from ready-to-eat food / Hossein Jamali - Jamali, Hossein (2013)
Listeria monocytogenes (L. monocytogenes) is an important cause of listeriosis, a common foodborne disease of public health importance. Ready-to-eat (RTE) foods are known as a potential source of listeriosis. There are limited studies in the characterisation of L. monocytogenes in Malaysia. The objectives of the study were to determinate the prevalence of Listeria species and L. monocytogenes in RTE foods in Malaysia and to characterise these isolates by using molecular methods. Two hundred fifty RTE food samples, including cooked beef and beef products, beverages, cooked chicken and chicken products, fried egg and egg products, packed lunch, salad and vegetables, and cooked seafood and seafood products were purchased from hawkers and hypermarkets in Kuala Lumpur and Petaling Jaya. Conventional and molecular methods were used for the isolation of Listeria spp. and L. monocytogenes. Overall, out of 250 RTE food samples, Listeria species were found in 52 (20.8%) samples, of which 32 (61.5%) contained L. monocytogenes. Twenty-one (65.6%), 7 (21.9%) and 4 (12.5%) of L. monocytogenes isolates were grouped into serogroups “1/2a, 3a”, “1/2c, 3c” and “4b, 4d, 4e”, respectively. All the L. monocytogenes harbored virulence genes (inlA, inlB, inlC and inlJ) as confirmed by PCR and DNA sequence analysis. PCR-RFLP of the inlA, inlB and inlC had limited variation. Multi-drug resistance was observed in one isolate (3.1%) which belonged to serogroup “4b, 4d, 4e”. REP-PCR, BOX-PCR, RAPD and PFGE were performed to genetically characterise the L. monocytogenes isolates. Twenty-eight REP profiles, 31 BOX profiles, 32 RAPD profiles and 20 pulsotypes (PFGE profiles) were observed. These L. monocytogenes isolates were classified into 8, 9, 4 and 7 distinct clusters at 80% similarity by REP-PCR, BOX-PCR, RAPD and PFGE, respectively. The iii discriminatory power was 0.992, 0.998, 1.000 and 0.916 for REP-PCR, BOX-PCR, RAPD and PFGE, respectively. In summary, the prevalence rate of serogroup “4b, 4d, 4e” indicated that RTE foods are potential sources of listeriosis in humans and the presence of the internalin genes and multi-drug resistant L. monocytogenes indicated that contamination of RTE foods could be a public health concern. REP-PCR, BOX-PCR and PFGE could distinguish the L. monocytogenes isolates with different flagella antigen groups or serogroups.